The Value of Community Participation in the Creation of Local Legal Products in Indonesia - Solehudin, Ending; Fautanu, Idzam; Rizal, Lutfi Fahrul (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2024)
This research aims to explore the influence of community participation on the creation of local legal products in Indonesia, focusing on regions with special autonomy status like Banda Aceh, Aceh Besar Regency, Yogyakarta City, and Surakarta City, and comparing them with regions with ordinary autonomy status like Bandung Regency and Bandung City. Using a combined normative and empirical legal research approach, including public consultations and field surveys, the study delves into the origin of regional legal products, highlighting community participation, people's sovereignty, the rule of law, and public policy. It examines various factors affecting community involvement, such as social, political, cultural, and educational factors. The research findings underscore the importance of community participation in shaping the quality and compliance of local legal products. However, conventional patterns in facilitating community involvement often result in suboptimal participation, except for unique cases like Aceh, which demonstrates innovative approaches and impactful outcomes. The study concludes that enhancing community participation is crucial for improving the quality and effectiveness of local legal products, ensuring better compliance and implementation at the grassroots level.